Findings in Historical Control Harlan RCCHanTM: WIST Rats from 4-, 13-, 26-Week Studies. (April 2013) - Blankenship, Brad; Skaggs, Hollie
Vehicle control Harlan RCCHan™: WIST rats were examined to provide control data for subsequent studies. Sixty male and 60 female rats were sacrificed after 4, 13, and 26 weeks (360 animals total) of daily oral gavage dosing with reverse osmosis water. At necropsy, body weights, organ weights, and macroscopic findings were recorded, and tissues were collected for histopathology. Mean terminal body and organ weight data demonstrated expected age-related trends. Macroscopic findings occurred sporadically, generally at singular or at very low incidence, and with no observable age-related trend. The most frequent observation was discoloration of the stomach mucosa. Neoplastic microscopic findings were uncommon (one endometrial stromal polyp; one hepatocellular adenoma; one C-cell adenoma; and one sarcoma, NOS). The most common and/or notable nonneoplastic microscopic findings included basophilic tubules and mononuclear cell infiltration in the kidney, macrophage infiltration in pulmonary alveoli, and mononuclear infiltration in the liver of males and females, and myocardial degeneration/necrosis and mononuclear cell infiltration in the heart of males. Female reproductive tracts were staged to establish a representative baseline distribution. Diestrus, proestrus, estrus, and metestrus were diagnosed 45.8%, 11.9%, 30.5%, and 11.9%, respectively, at 4 weeks and 27.6%, 13.8%, 50.0%, and 8.6%, respectively, at 13 weeks.